DESIGN AND CONSTRUCTION OF METALLURGICAL MICROPLANT - A. B. Steblov; S. N. Berezov; M. M. Tairbekov; I. V. Dubrova (Литьë и металлургия)
The experience of design and construction of micro factory which is focused on production of building bar is briefly stated.